Parameters determination and error compensation for low-cost piezoresistive sensor measurements - R. S. Raihan, S. (International Journal of Engineering and Technology, 2019)
A calibration algorithm of pressure sensor for estimation of parameters and error compensation is presented in this paper. Voltage values corresponding to temperatures and pressures are measured to obtain the seven parameters for four calibration equations. Calculation of the calibration coefficients is done in the LabView environment, and these seven coefficients are stored inside a 16-bit microcontroller non-volatile data memory. For low-cost implementation, the pressure values are processed within the program memory with the size of only 8kB. As a result, the measurement of voltages from pressure and temperature sensors via the microcontroller can be executed and transmitted back to LabView. Â